SAFE TELECONSULTATION CHECK LIST: A TOOL THAT CAN IMPROVE TELEMEDICINE AND TELEPEDEUTICS - Cicero da Silva, Luciano; Carolina Botto Barros Félix, Ana; de Oliveira Alexandre, Anderson; Nascimento, Andrea; José de Andrade, Antônio; César Santos Oliveira, Bruno; de Fátima Rodrigues Sena, Maria; Teresa Pinheiro, Maria; de Fátima Figueroa Bohórquez, Karen; Raimundo Ernesto Machado, Sérgio (Health and Society, 2023)
This article explores the role of telemedicine, a discipline that integrates the foundations of traditional medical practice with communications technology to provide healthcare at a distance. It examines the associated challenges, the opportunities offered and the future perspectives of medical propaedeutics in an increasingly digital scenario. Based on these aspects, the article proposes the use of a checklist as fundamental support for telemedicine. In summary, teleconsultation supported by a didactic and safe tool represents not only an evolution in the provision of healthcare, but also a testimony to the technology’s ability to provide an effective and patient-centered clinical experience. This new paradigm not only addresses the complexities of virtual consultation, but also shapes the future of medicine by embracing the potential of safe use of technology.